Wildland fire emission sampling at Fishlake National Forest, Utah using an unmanned aircraft system. (15th February 2021) - Aurell, J.; Gullett, B.; Holder, A.; Kiros, F.; Mitchell, W.; Watts, A.; Ottmar, R.
Abstract: Emissions from a stand replacement prescribed burn were sampled using an unmanned aircraft system (UAS, or "drone") in Fishlake National Forest, Utah, U.S.A. Sixteen flights over three days in June 2019 provided emission factors for a broad range of compounds including carbon monoxide (CO), carbon dioxide (CO2 ), nitric oxide (NO), nitrogen dioxide (NO2 ), particulate matter < 2.5 μm in diameter (PM2.5 ), volatile organic compounds (VOCs) including carbonyls, black carbon, and elemental/organic carbon. To our knowledge, this is the first UAS-based emission sampling for a fire of this magnitude, including both slash pile and crown fires resulting in wildfire-like conditions. The burns consisted of drip torch ignitions as well as ground-mobile and aerial helicopter ignitions of large stands comprising over 1000 ha, allowing for comparison of same-species emission factors burned under different conditions. The use of a UAS for emission sampling minimizes risk to personnel and equipment, allowing flexibility in sampling location and ensuring capture of representative, fresh smoke constituents. PM2.5 emission factors varied 5-fold and, like most pollutants, varied inversely with combustion efficiency resulting in lower emission factors from the slash piles than the crown fires. Graphical abstract: Image 1 Highlights: An unmanned aircraft system was used to measure air pollutants from a wildland fire. The prescribed fire included slash pile burns and crown fires. Emission factors were determined for a comprehensive list of gases and particles. Emissions typically decreased with increasing combustion efficiency. The system enabled unprecedented access to the fire while minimizing risk.